METHODS AND SYSTEMS CONTROL THE SUPPORTS OF THE TUBULAR RODS USED IN THE ENERGY CONSTRUCTION WHEN EXPOSED TO STATIC AND DYNAMIC LOADS - I. Z. Gatiyatov; L. S. Sabitov (Известия высших учебных заведений: Проблемы энергетики)
The article presents the methods and installations of control supports tubular rods used in power construction when exposed to static and dynamic loads. Test methods are described.